Penggunaan Prototype Media Pembelajaran Untuk Anak Usia Dini Menggunakan Teknik Scan Tiga Dimensi - Hanifah Rahmi Zatalina (Besaung : Jurnal Seni Desain dan Budaya, 2024)
This research creates a prototype of learning media for early childhood using 3D scanning techniques. The prototype is designed to introduce the variety of endemic fauna in Indonesia. The research method is Analysis, Design, Development, Implementation, and Evaluation (ADDIE). This learning media is designed with five stages: Analyzing the proximity between children and technology, designing animal icons and maps, designing a 3D scan prototype using Polycam Pro, testing the 3D Scan prototype, implementation of the 3D Scan prototype. Designing a 3D Scan using Polycam Pro is better using manual methods to produce images with clear textures. 3D Scan design using Polycam Pro produces 3D shapes of endemic animal objects that are published on the web as learning media for early childhood.